Feasibility Building Structures of PT. Suri Tani Pemuka Cirebon - Firmanto, Arief (International Journal for Educational and Vocational Studies, 2019)
The condition of the building in the building of PT. Suri Tani Pemuka Cirebon experienced a few problems in building material components such as materials made of steel which have begun to show the presence of corrosion in steel. This is caused, among others, from the negligence of poorly controlled boiler engine settings. thus raising issues regarding eligibility in building structures. This study aims to determine the residual strength, deflection value, and interstory drift in building structure components and to determine the level of structure safety in the existing building conditions. The flowchart is carried out starting with a field assessment then a literature study continues with measurement and analysis assessment, followed by analysis, conclusions and finishing. From visual observation and structure calculation, the structure of plant 1, plant 2 and warehouse, is still functioning well and is suitable for use as long as there is no corrosion and technical disturbance that occurs.